Pengaruh Tiamin, IMT, Durasi Tidur terhadap Gejala Kecemasan pada Pasien Gangguan Neurosis, Stress, dan Somatoform - Lintang Mega Pertiwi; Mohammad Fanani; Nur Hafidha Hikmayani (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Neurotic, stress, and somatoform disorders are one of the diagnosis group characterized by anxiety symptoms. Thiamine or vitamin B1 levels, Body Mass Index (BMI), and sleep duration have been associated partially with anxiety disorders in the health population. The aim of this study is to examined the relationship between thiamine levels, BMI, and sleep duration with anxiety symptoms among people with neurotic, stress, and somatoform disorders. This study is observational with cross-sectional design and engage patients with neurotic, stress, and somatoform disorders as participant. The data gathered comprised thimine levels measured using the liquid chromatography-mass spectrometry (LC-MS/MS), BMI measured based on data of the patient's weight and height, and sleep duration obtained through a questionnaire. Anxiety levels were evaluated using the Zung Self-Rating Questionnaire (SAS). Linear regression was performed for data analysis. The findings indicated that there was no significant relationship between vitamin B1 levels and anxiety levels. However, this study suggested that an increase of 1 hour in sleep duration (coefficient = -2.784, p = 0.007) and an increase of 1 unit in BMI (coefficient = -0.824, p = 0.022) were associated with a statistically significant decrease in anxiety index. This study demonstrated significant relationship between BMI and sleep duration with anxiety symptoms in patients with neurotic, stress, and somatoform disorders. Further study is required to understand the mechanisms of this relationship and its implications for the treatment of patients with neurotic, stress, and somatoform disorders.